Situación de salud de las comunidades indígenas Nasas, Santander de Quilichao, Cauca, Colombia, 1999-2000 (2002)
ABSTRACT: A study was carried out with a descriptive design including a cross section, which was complemented with a qualitative ethnographic analysis about health conditions and perceptions of health services in four indigenous communities. With the participation of the network of health promoters and voluntary indigenous assistants 211 family survey were applied. The Nasas indigenous communities showed had a poor health status, mainly protruding in poor sanitary conditions in their homes, with diseases such as acute diarrheal, respiratory infection, skin infections and tuberculosis. The social security health system covered a high proportion of population mainly through subsidiary regime, but even though they had an indigenous enterprise for health assistance, they also faced difficulties to access collectively to institutional health services.